Using a Portfolio as an Alternative and Authentic Tool of Assessment - DERRADJI, Saleh (Journal of Human Sciences, 2009)
Traditional methods of testing which still prevail in our system of education mean that there is very little time for conversational English in the tests-driven in classrooms, despite of the emergence of recent advances in language testing methodology. This paper suggests to examine and understand how and why a portfolio can be used as an alternative and authentic tool of oral assessment .We believe that through this testing technique and with the investment and commitment of the pedagogical team, we will be able to develop genuine oral communication in the learners and promote a new vision of measurement